2011
DOI: 10.1080/13546805.2010.524494
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of verbal learning impairment and recovery in a marijuana-dependent male: The effects of sustained marijuana abstinence

Abstract: We present the case of a young adult in treatment for marijuana dependence, with recurrent depression and a history of possible TBI, complaining of concentration, memory and initiation problems. Testing at treatment baseline revealed performance that was generally in the High Average range on measures of reaction time and attention, with a selective impairment in verbal learning (Borderline to Extremely Low range). Following 8 weeks of abstinence from marijuana, his verbal learning recovered to expected levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…The finding that verbal learning decrements were modestly associated with marijuana use is consistent with a considerable amount of literature demonstrating that: (i) verbal learning performance is decreased in active marijuana users (1,19,20), (ii) verbal learning performance is inversely correlated with severity measures of use (4,21), and (iii) verbal learning performance improves with increasing abstinence (2224). However, the finding that verbal learning was not further decreased in participants with a comorbid depressive disorder was unexpected, considering that some studies have found that verbal memory function is decreased in non-marijuana-using depressed individuals (7,9,11).…”
Section: Discussionsupporting
confidence: 86%
“…The finding that verbal learning decrements were modestly associated with marijuana use is consistent with a considerable amount of literature demonstrating that: (i) verbal learning performance is decreased in active marijuana users (1,19,20), (ii) verbal learning performance is inversely correlated with severity measures of use (4,21), and (iii) verbal learning performance improves with increasing abstinence (2224). However, the finding that verbal learning was not further decreased in participants with a comorbid depressive disorder was unexpected, considering that some studies have found that verbal memory function is decreased in non-marijuana-using depressed individuals (7,9,11).…”
Section: Discussionsupporting
confidence: 86%